Conversion and Identity The Pastoral Care and Discipleship of Converts from Islam in the Context of the UK. - Malik, Saira (Regnum Books International, 2022)
After researching conversion to and from Islam, this book suggests that misunderstanding surrounds groups of converts from Islam. However, converts should be heard as they understand the perspectives of both traditions, and are potential agents for cross-cultural dialogue and mediation. The book's overarching theoretical framework focuses on the themes of conversion and identity. It records and analyses the experiences of converts from Islam to Christianity, and those who care for converts, in respect of their own discipleship paths and the handling of pastoral care in the UK. The hypothesis i.